Metal‐Organic Frameworks: In Situ Reversible Ionic Control for Nonvolatile Magnetic Phases in a Donor/Acceptor Metal‐Organic Framework (Adv. Funct. Mater. 5/2017). (February 2017) - Taniguchi, Kouji; Narushima, Keisuke; Sagayama, Hajime; Kosaka, Wataru; Shito, Nanami; Miyasaka, Hitoshi
Abstract : In article 1604990, K. Taniguchi, H. Miyasaka, and co‐workers demonstrate reversible magnetic phase switching between the ferrimagnetic and paramagnetic states of an electron‐donor/‐acceptor metal–organic framework (D/A‐MOF) using Li + ‐ion battery (LIB) cycles. The D/A‐MOF material incorporated into the cathode of LIB undergoes a band‐filling electronic modification when Li + ‐ions and electrons are simultaneously inserted into/extracted from the cathode.